2021
DOI: 10.1029/2020jd034204
|View full text |Cite
|
Sign up to set email alerts
|

Observed Vertical Structure of Precipitation Influenced by Dry Air for Landfalling Tropical Cyclones Over China

Abstract: The vertical structure of precipitation and its evolution during midlevel dry‐air intrusion (DAI) for landfalling tropical cyclones (LTCs) over China in the past 10 years were examined using several observed Tropical Rainfall Measuring Mission (TRMM) PR products and a reanalysis data set. We show that in the outer region where the environmental midlevel dry air intrudes more easily, the process of environmental DAI has an important effect on the vertical structure and precipitation of LTCs through promoting su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Previous findings (Shu et al, 2014(Shu et al, , 2018(Shu et al, , 2021 revealed important effects of dry air on the precipitation of LTCs, including reducing convective available potential energy and suppressing deep convective development by promoting evaporative cooling and enhancing the cold downdraft in the boundary layer. The results obtained here deepen the previous findings by presenting an additional radiation-related effect of dry air which lows the TC's environmental humidity, then influences the optical properties of underlying SSAs and finally reduces the updraft and rainfall of the TC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous findings (Shu et al, 2014(Shu et al, , 2018(Shu et al, , 2021 revealed important effects of dry air on the precipitation of LTCs, including reducing convective available potential energy and suppressing deep convective development by promoting evaporative cooling and enhancing the cold downdraft in the boundary layer. The results obtained here deepen the previous findings by presenting an additional radiation-related effect of dry air which lows the TC's environmental humidity, then influences the optical properties of underlying SSAs and finally reduces the updraft and rainfall of the TC.…”
Section: Discussionmentioning
confidence: 96%
“…When a TC moves from the far open sea to the coastal region, it is usually intruded by environmental dry air from the continent on the west or the WNPSH to the north (Shu et al, 2014(Shu et al, , 2018(Shu et al, , 2021. Fitow made landfall in Zhejiang Province of Southeast China at 1715 UTC 6 October 2013.…”
Section: Process Of Dry-air Intrusion For Typhoon Fitowmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind vectors backed with height generally implied dry air intrusion (Figures 9b and 9c). Shu et al (2021) pointed out that this may be an additional reason the upper-level divergence and deep convection strengthened and produced the TLEs. An additional premise to consider is that the TLE producing cell during Case I exhibited the strongest cloud top divergence.…”
Section: Discussion Of Rainband and Eyewall Lightning Eventsmentioning
confidence: 99%
“…This study focuses on the urbanization effect on TCP in the GBA during TC landfall. Following previous studies (Feng & Shu, 2018; Shu et al., 2021), we investigate the TCP characteristics from 18 hr prior to TC landfall to 24 hr after TC landfall. To simulate the TC landfall well and reduce the error caused by the initial conditions to the uncertainty of the physical quantities of the model (T. Yang et al., 2018), the model begins to run at almost 24 hr prior to TC landfall, and ends at around 24 hr after TC landfall.…”
Section: Methodsmentioning
confidence: 99%